2017
DOI: 10.1186/s12957-017-1229-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes of hepatectomy for stage B Hepatocellular carcinoma in the BCLC classification

Abstract: BackgroundBecause hepatectomy is not recommended in patients with stage B hepatocellular carcinoma (HCC) of the Barcelona Clinic Liver Cancer (BCLC) staging, we evaluated the survival outcomes of hepatectomy for stage B in the BCLC system.MethodsData were collected from 297 consecutive adult stage B patients who underwent curative hepatectomy for HCC between 1996 and 2014 in Hokkaido University Hospital. Overall survival (OS), disease-free survival (DFS), and risk factors were analyzed using the Kaplan–Meier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…AFP was not a strong prognostic marker despite the fact that serum AFP level above 400 ng/ml would indicate poor overall survival time after hepatectomy in patients with HBV-associated HCC [38]. Some studies reported that combined analysis enhanced diagnosis and prognosis value of AFP in HCC [39,40]. Our results suggested joint analysis of AFP, p53 and VEGF might be performed for the prediction of the clinical outcomes of HBV-related HCC patients in Guangxi.…”
Section: Discussionmentioning
confidence: 61%
“…AFP was not a strong prognostic marker despite the fact that serum AFP level above 400 ng/ml would indicate poor overall survival time after hepatectomy in patients with HBV-associated HCC [38]. Some studies reported that combined analysis enhanced diagnosis and prognosis value of AFP in HCC [39,40]. Our results suggested joint analysis of AFP, p53 and VEGF might be performed for the prediction of the clinical outcomes of HBV-related HCC patients in Guangxi.…”
Section: Discussionmentioning
confidence: 61%
“…The clinical grading systems for HCC prognosis include Barcelona clinic liver cancer (BCLC) staging, 11 Okuda staging, 12 tumor-node-metastasis (TNM) staging, 13 and albumin-bilirubin (ALBI) grading, 14 and they consider factors such as tumor size, number of lesions, vascular invasion, extrahepatic metastases, and common clinical and pathological factors such as Child-Pugh classification. However, none of these grading systems take into account the inflammatory status of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection was recognized as the last but not least option for these patients to obtain long-term survival [ 2 , 3 , 5 , 6 ]. Several studies have reported that radical resection of the tumor and involved vessels can prolong survival and may eventually offer a chance of cure in selected cases [ 3 , 12 , 24 , 25 ]. However, even in these areas, there is still controversy over optimum treatment strategy for HCC patients in these stage, regardless guidelines for practice.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been several studies and meta-analysis accessing HR and TACE in the management of intermediate or advanced stage of HCC [ 25 , 40 44 ]. However, to our knowledge, the study we presented here was one of the several studies to access the survival outcome of HR versus TACE in UICC/AJCC stage IIIa/IIIb HCC patients [ 12 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%